2021
DOI: 10.3389/fpsyg.2021.769054
|View full text |Cite
|
Sign up to set email alerts
|

Falling in Love With Work: The Effect of Enterprise Social Media on Thriving at Work

Abstract: Using a survey of 300 employees in different types of enterprises and different positions, this study verified that the use of enterprise social media has a positive effect on employees’ work exuberance. The study separately examined the effects of social media applications for work tasks and social tasks. Both types of applications had a positive impact on employees’ work exuberance. The study also identified the mediating role of challenge and obstructive stressors in this relationship. Work-related social m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…More specifically, we found no statistically relevant correlation between the two, which contradicts the aforementioned findings. However, even though these results differ from some earlier published works, they seem to be consistent with Zheng and Davidson 86 and Liu et al 87 …”
Section: Discussioncontrasting
confidence: 61%
“…More specifically, we found no statistically relevant correlation between the two, which contradicts the aforementioned findings. However, even though these results differ from some earlier published works, they seem to be consistent with Zheng and Davidson 86 and Liu et al 87 …”
Section: Discussioncontrasting
confidence: 61%
“…Zheng and Davison [ 82 ] concluded that work-related social media use increased employees’ affectionate identification with the team and enhanced the sense of teamwork. Furthermore, Liu et al [ 83 ] concluded that this behavior increases employees’ enthusiasm for work. Specifically, the use of work-related social media increased employee enthusiasm by reducing obstructive stressors, while the use of social-related social media increased employee enthusiasm by reducing challenging stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The second is work stress. Liu et al [ 83 ] found the mediating role of challenging and hindering pressures; i.e., challenging pressures positive mediate employees’ work enthusiasm, while hindering pressures are negatively mediating with employees’ work enthusiasm. The third variable is work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…If they responded successfully to these screening questions, the participants could continue to complete the survey itself. Our study uses cross-sectional data mainly because it is commonly used in the area of human-computer interaction ( Chong et al, 2018 ; Lazaroiu et al, 2020 ; Liu et al, 2021 ), making the results comparable and generalizable. Thus, the conclusions of this study are more convincing in the contribution they make to the field, due to the use of data of the same nature.…”
Section: Methodsmentioning
confidence: 99%